THE LINGUISTIC REPRESENTATION OF THE CONCEPT OF PEACE IN MODERN UZBEK AND ENGLISH LITERATURE: A COMPARATIVE ANALYSIS - O’rmonovа Durdonаxon (Modern American Journals, 2025)
This article offers a comparative linguistic analysis of how peace and its opposites are represented in modern Uzbek poetry and selected works of English literature. Using a combined framework of cognitive semantics, pragmatics, and cultural linguistics, the study focuses on textual samples from Erkin Vohidov and Abdulla Oripov (Uzbek literature) and George Orwell (1984) and Ernest Hemingway (A Farewell to Arms) to examine: lexical fields and collocations associated with peace; metaphorical and image‑schematic structures; evaluative language including irony, idealism, ambivalence; and the influence of cultural‑historical experience on these representations.
Keywords: Peace; linguistic representation; conceptual metaphor; comparative literature; Uzbek poetry; English literature; Erkin Vohidov; Abdulla Oripov; George Orwell; Ernest Hemingway; cognitive linguistics; cultural linguistics; conceptual semantics; evaluative language; ideological discourse; war and peace; national identity; spiritual harmony; cross-cultural analysis; translation studies